Analisis Hubungan Antara Tingkat Kecanduan Smartphone dan Tingkat Aktivitas Fisik dengan Kebugaran Fisik: Studi Kasus Mahasiswa Universitas di Papua - Kardi, Ipa Sari; Ansar CS; Jofri Julio Juventus Samberi; Nosina Pagawak; Nusmin Kogoya; Fransisco Dedhicko Renwarin Rumbekwan; Tarbak Bidana (UNIB Press, 2025)
The use of smartphones, if not properly controlled, will also hurt the population of Papua, especially students who are more prone to smartphone addiction. This study aims to determine the level of smartphone addiction and the relationship between physical activity and physical fitness among students in Papua. The method used is a quantitative correlation analysis design. The sample consisted of 91 university students (73 males and 18 females) selected using a stratified proportional random sampling method. Data collection techniques included the Smartphone Addiction Scale (SAS), which is a valid and reliable instrument with a Cronbach's Alpha value of 0.848, the International Physical Activity Questionnaire (IPAQ), and the Rockport Test to assess students' physical fitness. The results showed that the level of smartphone addiction was moderate (57.1%), the respondents' level of physical activity was mostly high (61.5%), and their level of physical fitness was mostly good (47.9%). The conclusion showed a significant correlation between the variables with a P value < 0.05. Based on the research findings, it is recommended that students increase their physical activity levels to reduce smartphone use and improve their physical fitness.